2022
DOI: 10.1002/lio2.954
|View full text |Cite
|
Sign up to set email alerts
|

Patient injuries from tonsil and adenoid surgery in Finland

Abstract: Objectives: The aims of this national register-based study were to examine patient injury claims related to tonsil and adenoid surgery injuries and to compare the frequency of claims between tonsillectomies and tonsillotomies in Finland. Methods:We analyzed the complaints related to tonsil and adenoid surgery received by the Finnish Patient Insurance Center (PIC) between the years 2000 and 2019.One hundred seventy-two cases were included in the analysis. The annual surgery rates between the years 2000 and 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Two studies used national registries to evaluate the difference in complication rates related to tonsillectomy techniques. A registry of tonsillectomies performed in Finland between 2000 and 2018 showed 172 claims based on patient injuries as a result of the surgery [14 ▪ ]. Only 1.7% of claims were made after ICT as opposed to ECT, and the seven reported deaths were after ECT, exclusively [14 ▪ ].…”
Section: Safety and Regrowthmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies used national registries to evaluate the difference in complication rates related to tonsillectomy techniques. A registry of tonsillectomies performed in Finland between 2000 and 2018 showed 172 claims based on patient injuries as a result of the surgery [14 ▪ ]. Only 1.7% of claims were made after ICT as opposed to ECT, and the seven reported deaths were after ECT, exclusively [14 ▪ ].…”
Section: Safety and Regrowthmentioning
confidence: 99%
“…A registry of tonsillectomies performed in Finland between 2000 and 2018 showed 172 claims based on patient injuries as a result of the surgery [14 ▪ ]. Only 1.7% of claims were made after ICT as opposed to ECT, and the seven reported deaths were after ECT, exclusively [14 ▪ ]. In addition, a database review of English hospitals exclusively employing coblation ICT showed a 1.2% readmission rate and 0.2% reoperation rate for posttonsillectomy hemorrhage [15 ▪ ].…”
Section: Safety and Regrowthmentioning
confidence: 99%